Affecting photographies - Phu, Thy; Steer, Linda (Oxford : Berg, 2009)
Intends to rebalance the over emphasis on art historical approaches, to look at vernacular and applied photography. This book covers the historical, technological, cultural and social aspects of photography, as well as all genres.
Special Issue: Affecting Photographies Guest edited by Thy Phu and Linda M. Steer Articles Introduction. Thy Phu and Linda M. Steer Archive and Affect in Contemporary Photography Sarah Bassnett De Meyer at Vogue: Commercializing Queer Affect in First World War-era Fashion Photography Elspeth H. Brown Citizenship, Diaspora and the Bonds of Affect: The Passport Photograph Lily Cho Sontag's Lament: Emotion, Ethics, and Photography Sarah Parsons On Photographic Violence Sharon Sliwinski Review Essay A Rupture in the Field of Representation: Animals, Photography and Affect Matthew Brower Review Essay The Performative Force of Photography Laura Levin The Archive Cumulative Affect: Museum Collections Photography, and Studio Portraiture Deepali Dewan and Sophie Hackett
Special issue
boek